Wood fiber glass cement board - Fauzi, Fatin Nadzirah (2022)
A wall is one of the buildings components. Globally, the usage of concrete panel walls in buildings are increasing significantly. The precast concrete panel wall is a flexible component that may be utilized in building design as structural, an architectural or a mix of both. Prefabricated concrete wall panel as previously indicated, can be constructed as load bearing or non-load bearing components. Therefore, wall panel have replaced traditional walls as the preferred choice due to its ability to speed up the construction process, provide dependable quality control and be cost effective. In addition, panel walls are mass produced in factories or in open areas near the building sites. After a few days, the wall panels are old and sturdy enough to use and the quality is also controlled based on the calculations (Muhammad Ujianto, Ahmad Zurisman Mohd Ali, Mohamad Solikin, 2019).